2015
DOI: 10.1039/c5cp01227a
|View full text |Cite
|
Sign up to set email alerts
|

An electrochemical investigation of rutile TiO2 microspheres anchored by nanoneedle clusters for sodium storage

Abstract: Rutile TiO2 microspheres anchored by nanoneedle clusters, as a new class of anode materials, are successfully employed for sodium-ion batteries and manifested good energy storage behavior. The initial discharge capacity of 308.8 mA h g(-1) is obtained and a high reversible capacity of 121.8 mA h g(-1) is maintained after 200 cycles at a current density of 0.1 C, exhibiting a high capacity retention of 83.1%. All these merits are not only ascribed to the rutile TiO2 crystal structure, but also thanks to the por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
56
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 41 publications
(64 reference statements)
8
56
0
Order By: Relevance
“…We considered (100) and (111) reconstructed surfaces. We found that Li insertion barriers into (100) and (111) bare surfaces are about 1 and 1.1 eV, respectively. These are much larger barriers than the well-studied diffusion barriers of Li in bulk Si, which are on the order of 0.5 eV, and could be the kinetic bottleneck in initial stages of lithiation.…”
Section: Interactions Of LI Na K and Mg With Monoelemental Group Imentioning
confidence: 89%
See 4 more Smart Citations
“…We considered (100) and (111) reconstructed surfaces. We found that Li insertion barriers into (100) and (111) bare surfaces are about 1 and 1.1 eV, respectively. These are much larger barriers than the well-studied diffusion barriers of Li in bulk Si, which are on the order of 0.5 eV, and could be the kinetic bottleneck in initial stages of lithiation.…”
Section: Interactions Of LI Na K and Mg With Monoelemental Group Imentioning
confidence: 89%
“…These barriers can be significantly changed by the presence of EC: the EC molecule can adsorb on these surfaces in a molecular, semi-dissociated (SD) configuration or a ketone-like configuration, with a preference for SD. The SD configuration, whose formation is very exothermic, lowers the insertion barrier of a neighboring Li atom by about 0.2 eV on the (100) surface but raises it by a similar amount on (111). The ketone-like configuration, however, which is only by about 0.2 eV less stable on the (111) surface, raises the barrier by 0.4 eV.…”
Section: Interactions Of LI Na K and Mg With Monoelemental Group Imentioning
confidence: 92%
See 3 more Smart Citations